EXPRESSIVE ILLOCUTIONARY ACT OF THE JUDGES IN THE BRITAIN’S GOT TALENT AUDITION 2022 - Sang Ayu Dwi arinda Wedawati; Putu Nur Ayomi (IKIP Siliwangi, 2023)
This research aims to find out the types of expressive Illocutionary acts used by the judges in Britain's Got Talent audition 2022 based on the theory proposed by Searle (1979), and to identify the function of expressive Illocutionary acts based on the theory of Leech (1983). This research employed a descriptive quantitative approach to further explain the data. Data from the results of the study indicated that are five different types of expressive Illocutionary acts performed by the judges: praising is the highest followed by thanking, congratulating, blaming and apologizing. Moreover, there are only two functions of illocutionary acts found. They were convivial and conflictive functions. The most dominant in this category was convivial function, because the comments that are most often found use polite language and do not offend listeners. Keywords: Expressive; Illocutionary Act; Britain’s Got Talent